2019
DOI: 10.2478/jvetres-2019-0058
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus – persistence in different environmental conditions and the possibility of its indirect transmission

Abstract: Since 2007, African swine fever (ASF) has posed a serious threat to the European swine industry. In Poland, the numbers of reported outbreaks in pigs and affected areas grow every year. In 2018, the disease was noted in Western Europe, in Belgium specifically, where several hundred infected wild boars have been detected so far. In 2018, the virus unexpectedly emerged in pig holdings in eastern China, northern Mongolia, Vietnam, and Cambodia, causing worldwide concern about its further spread. Since there is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
135
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(149 citation statements)
references
References 47 publications
2
135
0
12
Order By: Relevance
“…All sampled carcasses were buried for at least one summer period, and in case of advanced decomposition status at time of burial ( Figure 2) it can be assumed that the exposure to outdoor conditions was even longer. ASFV is known to be heat sensitive (Plowright & Parker, 1967) and inactivated at 37°C after around 20 days (Mazur-Panasiuk, Zmudzki, & Wozniakowski, 2019). Therefore, taking into consideration the additional temperature increase of the carcass during decomposition (above 32°C at an outer temperature of 23°C) it does not seem unlikely that the virus has been inactivated effectively during the decomposition process (Johnson, Mikac, & Wallman, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All sampled carcasses were buried for at least one summer period, and in case of advanced decomposition status at time of burial ( Figure 2) it can be assumed that the exposure to outdoor conditions was even longer. ASFV is known to be heat sensitive (Plowright & Parker, 1967) and inactivated at 37°C after around 20 days (Mazur-Panasiuk, Zmudzki, & Wozniakowski, 2019). Therefore, taking into consideration the additional temperature increase of the carcass during decomposition (above 32°C at an outer temperature of 23°C) it does not seem unlikely that the virus has been inactivated effectively during the decomposition process (Johnson, Mikac, & Wallman, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important steps when performing "feed and water biosecurity" is disinfection, and it may reduce or inhibit the risk of the ASFV contamination in the environment or other pathogens [31]. Recent report demonstrated that the ASFV could be directly transmitted to contract pigs by contaminated fomites, drinking water, facilitate pig industry [12], excretions [13], and carriers [14]. The minimum infectious doses of ASFV for water via the oronasal route was estimated to be 10 0 TCID 50 , respectively, suggesting that the small amount of infective material could lead to ASFV transmission to the healthy pig industry [11].…”
Section: Resultsmentioning
confidence: 99%
“…The recent results demonstrated that ASFV could be easily transmitted orally through natural consumption of both liquid and feed, indicating the important role of feed in the emergence of ASFV outbreak in new pig populations throughout the world [11,12]. Disinfection and the proper use of disinfectants of pathogenic in feed and water are a basic and the most important role in the aspect of biosecurity and based on decreasing the percentage of pathogenic micro-organisms in the feed [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veterinary officials argue, however, that many of the current backyard facilities are hard or impossible to clean or disinfect, especially due to climatic conditions, and thus require a prolonged restocking period. Some research indeed suggests that the virus's stability in feces depends largely on the temperature and can extend beyond the suggested duration [9,10].…”
Section: Discussionmentioning
confidence: 99%